2002
DOI: 10.1046/j.1532-5415.2002.50205.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Depression in Older Patients After Myocardial Infarction

Abstract: Depression is prevalent after an acute MI in patients aged 65 and older. Older post-MI patients with depression have more comorbidities than older patients without depression and have almost four times the risk of dying within the first 4 months after discharge. Although this increased risk is likely to be related to many factors, our data suggest that sicker patients who are older and depressed may less often be prescribed medications known to reduce post-MI mortality and may also have greater difficulty foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 33 publications
5
75
0
3
Order By: Relevance
“…Consistent with our present results, previous longitudinal studies have reported no significant association between depression and baseline measures of cardiac disease severity, such as LVEF and Killip Class (15)(16)(17)(18)(19)(24)(25)(26)(27)(28), although some have reported a significant association (21,23). Our study adds to this literature by evaluating the association of depression with comprehensive measures of systolic function, diastolic function, inducible ischemia, and wall motion abnormalities.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with our present results, previous longitudinal studies have reported no significant association between depression and baseline measures of cardiac disease severity, such as LVEF and Killip Class (15)(16)(17)(18)(19)(24)(25)(26)(27)(28), although some have reported a significant association (21,23). Our study adds to this literature by evaluating the association of depression with comprehensive measures of systolic function, diastolic function, inducible ischemia, and wall motion abnormalities.…”
Section: Discussionsupporting
confidence: 81%
“…However, many prospective studies with the specific aim of investigating the association between depression and outcomes for patients with CHD have reported univariate associations between depression and disease severity measures at baseline. Some of these studies have reported an association between depression and lower LVEF and/or higher Killip Class (21,23), but many others have found no relationship between depression and various measures of cardiac disease severity (15)(16)(17)(18)(19)22,(24)(25)(26)(27)(28). In addition, prior studies that have found a relationship between depression and outcome have sampled patients after acute CHD events such as AMI (14,17,27,29) or CABG surgery (16,19).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological explanations have been proposed, including increased sympathetic activity, arterial atherosclerosis, and heart rate variability [14]. One important psychosocial factor is that depressed patients are less likely to adhere to recommendations for secondary prevention [15,16]. A recent meta-analysis across a range of medical conditions showed that non-adherence to medical treatment is three times more likely to occur with depressed than non-depressed patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study of 153 hospitalized patients interviewed 4 months after discharge, older post-myocardial infarction patients (X65 years) with depression were less likely to adhere to medication or modify their diet and exercise regularly than patients without depression. 25 ED, depression and CVD frequently co-occur and appear to share a number of risk factors; on this basis, a mutually reinforcing triad of the diseases has been proposed to play a significant role, increasing mortality and affecting the quality of life dramatically (Figure 2). 26 Reducing stress Emotional stress has a negative effect on the cardiovascular system.…”
Section: S16mentioning
confidence: 99%